PELATIHAN PEMBUATAN JAMU DAUN KATUK (SAUROPUS ANDROGYNUS) PELANCAR ASI SEBAGAI UPAYA MENSUKSESKAN GERAKAN ASI EKSKLUSIF DI KELURAHAN GUNUNG ANYAR SURABAYA - Retno Setyo Iswati; Yefi Marliandiani; Anik Latifah; Setiana Andarwulan (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2019)
Gunung Anyar is a village in Gunung Anyar, Surabaya Municipality. In this area the puerperal mother cannot breastfeed properly. One way to overcome this problem is to make herbal drinks from katuk leaves. Some houses in Kelurahan Gunung Anyar have enough area to plant katuk leaf seedlings. Training on making herbal drinks from katuk leaves can improve the skills of cadres and pregnant women. This activity can also build innovation and creativity in varying the utilization of katuk leaves. Method: This activity is carried out through demonstration of making herbal drinks with the target being cadres and pregnant women. Results: The results of the training were very good. All participants actively participate and can train other pregnant women to make herbal drinks from katuk leaves at home. Conclusion: Training can be done at home by pregnant and lactating mothers